random 1 c2; binomial 354 .261. let c2(2)=354-c2(1) random 1 c3; binomial 730 .261. let c3(2)=730-c3(1) random 1 c4; binomial 405 .261. let c4(2)=405-c4(1) random 1 c5; binomial 226 .261. let c5(2)=226-c5(1) random 1 c6; binomial 111 .261. let c6(2)=111-c6(1) random 1 c7; binomial 552 .261. let c7(2)=552-c7(1) random 1 c8; binomial 597 .261. let c8(2)=597-c8(1) rsum c2-c8 c9 let k2=c9(1)/(c9(1)+c9(2)) let c2(4)=k2*354 let c2(5)=354-c2(4) let c3(4)=k2*730 let c3(5)=730-c3(4) let c4(4)=k2*405 let c4(5)=405-c4(4) let c5(4)=k2*226 let c5(5)=226-c5(4) let c6(4)=k2*111 let c6(5)=111-c6(4) let c7(4)=k2*552 let c7(5)=552-c7(4) let c8(4)=k2*597 let c8(5)=597-c8(4) let c10(1)=(c2(1)-c2(4))**2/c2(4) let c10(2)=(c2(2)-c2(5))**2/c2(5) let c10(3)=(c3(1)-c3(4))**2/c3(4) let c10(4)=(c3(2)-c3(5))**2/c3(5) let c10(5)=(c4(1)-c4(4))**2/c4(4) let c10(6)=(c4(2)-c4(5))**2/c4(5) let c10(7)=(c5(1)-c5(4))**2/c5(4) let c10(8)=(c5(2)-c5(5))**2/c5(5) let c10(9)=(c6(1)-c6(4))**2/c6(4) let c10(10)=(c6(2)-c6(5))**2/c6(5) let c10(11)=(c7(1)-c7(4))**2/c7(4) let c10(12)=(c7(2)-c7(5))**2/c7(5) let c10(13)=(c8(1)-c8(4))**2/c8(4) let c10(14)=(c8(2)-c8(5))**2/c8(5) Let c11(k1)=sum(c10) let k1=k1+1